Case report: A healthy baby achieved after preimplantation genetic testing from an infertile woman with hereditary leiomyomatosis and renal cell cancer syndrome - Hu, Qianhui; Zhang, Qing; Guo, Mengxi; Ding, Haixia; Xi, Ji; Zhang, Meiling; Wang, Min; Zhang, Lin; Li, Shuyuan; Wu, Dandan; Li, Wen (Frontiers in Medicine, 2024)
Background: Hereditary leiomyomatosis and renal cell cancer (HRLLC) is a rare autosomal dominant inheritable disease caused by Fumarate hydratase (FH) gene germline mutation. It is speculated that for HRLCC infertility women with multiple uterine leiomyomas, preimplantation genetic testing may help block transmission of mutated FH gene during pregnancy.We present the case of a 26-year-old nulligravida with a history of early-onset uterine leiomyomatosis had a heterozygous nonsense mutation (NM_000143.4(FH): c.1027C>T(p.Arg343Ter)) in the HRLLC gene. After ovulation induction and in vitro fertilization, preimplantation genetic testing for monogenic disorders (PGT-M) on embryos revealed the absence of the pathogenic allele in two blastomeres. Uterine fibroids were identified before embryo transfer, leading to a submucosal myomectomy and long period of pituitary suppression by Gonadotropin-releasing hormone analogue (GnRHa). The patient achieved a healthy live birth after the second cycle of frozen-thawed embryo transfer.This case details the successful treatment of an infertile patient with an HRLLC family history, resulting in a healthy birth through myomectomy and PGT-M selected embryo transplantation.Our literature search indicates the first reported live birth after HRLLC-PGT-M.